L’anéantissement symbolique des Afro-brésiliens par l’Empire du Brésil dans les expositions universelles (1867-1889) - Daniel Malanski (Caravelle)
During the second half of the 19th century, the World’s Fairs were the largest mega-events in the world. Peripheral nations, European empires and their former colonies shared a physical space in which they could proudly exhibit their social and technological advances towards a utopian model of modern society. The recently created Empire of Brazil (1822-1889) took advantage of these opportunities to forge its own identity. Nevertheless, the Brazilian organizing committees of these events seemed uneasy with the fact that the country was one of the last nations in the Western Hemisphere which hadn’t abolished slavery. In this article, we have used the concept of symbolic annihilation (a term that comes from communication sciences) to analyze the means used by Brazilian committees to avoid the topic of slavery.